Normalisation‐based receiver using BCGM approximation for α‐stable noise channels. Issue 15 (1st July 2013) - Li, Xutao; Chen, Peng; Fan, Lisheng; Gao, Feifei
Abstract : Aiming at signal detection in α ‐stable ( SαS ) noise, a receiver with a new zero‐memory nonlinearity limiter (ZMNL) is designed. The proposed ZMNL serves to transform the SαS noise into a standard Gaussian one by using the bi‐parameter Cauchy‐Gaussian mixture (BCGM) model to approximate the SαS density. Simulation results indicate that the proposed receiver outperforms the conventional sub‐optimal receivers for α > 1.5.